ANALISIS POTENSI TEGAKAN BLOK PEMANFAATAN KPH DAMPELAS TINOMBO DI DESA KARYA MUKTI KECAMATAN DAMPELAS KABUPATEN DONGGALA - Gunawan, Indra; Hamzari, .; Wahid, Abd (Jurnal Warta Rimba, 2018)
Block utilization is block whicnh functiones as the planned area to utilize limitedly according with the provision of forest legislation in the area. Forest management is always addressed to get the optimum benefits, understand the advantage of forest, implies the maning of all any types of benefits that can produced by forest. The utilization of timber forest product on the stand forest for various purposes, which done of types that have high economic value. This study aimed at finding in potential of stand block utilization in Karya Mukti village on Model of KPH Dampelas Tinombo. The study used Systematic Sampling with Countinous Strip Sampling. Utilization block area is 40 Ha by size 400 m x 1000 m. The length lines 400 m, then it was divided into 4 plots, so each plots have area 20 m x 100 m or the intesity of the sampling 8%. Data analyzed quantitatively by calculating the stand volume of block utilization, the measured parameter is circumference, diameter and high free branch. The results obtained are there are 36 species with number of stems 293 stems of the highest diameter 60 cm and the lowest 20 cm. Meanwhile for the total number of plot potential on the block utilization 225,59 mÂ³, the total potential of stand are 40 Ha is 2.818 mÂ³/ha.Keywords: Analysis, Potential of Stand, Block Utilization, KPH Dampelas Tinombo